Polysialylation of the Synaptic Cell Adhesion Molecule 1 (SynCAM 1) Depends Exclusively on the Polysialyltransferase ST8SiaII in Vivo - Rollenhagen, Manuela (American Society for Biochemistry and Molecular Biology, 2012)
Polysialic acid is a unique carbohydrate polymer specifically attached to a limited number of glycoproteins. Among them is synaptic cell adhesion molecule 1 (SynCAM 1), a member of the immunoglobulin (Ig) superfamily composed of three extracellular Ig-like domains. Polysialylation of SynCAM 1 is cell type-specific and was exclusively found in NG2 cells, a class of multifunctional progenitor cells that form specialized synapses with neurons. Here, we studied the molecular requirements for SynCAM 1 polysialylation. Analysis of mice lacking one of the two polysialyltransferases, ST8SiaII or ST8SiaIV, revealed that polysialylation of SynCAM 1 is exclusively mediated by ST8SiaII throughout postnatal brain development. Alternative splicing of the three variable exons 8a, 8b, and 8c can theoretically give rise to eight transmembrane isoforms of SynCAM 1. We detected seven transcript variants in the developing mouse brain, including three variants containing exon 8c, which was so far regarded as a cryptic exon in mice. Polysialylation of SynCAM 1 was restricted to four isoforms in perinatal brain. However, cell culture experiments demonstrated that all transmembrane isoforms of SynCAM 1 can be polysialylated by ST8SiaII. Moreover, analysis of domain deletion constructs revealed that Ig1, which harbors the polysialylation site, is not sufficient as an acceptor for ST8SiaII. The minimal polypeptide required for polysialylation contained Ig1 and Ig2, suggesting an important role for Ig2 as a docking site for ST8SiaII.